2017
DOI: 10.1159/000471916
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Glandular Cells on Conventional Cervicovaginal Smears: Experience from a Tertiary Care Hospital in Coastal India

Abstract: Introduction: Glandular lesions of the female genital tract (FGT) are quite uncommon compared to squamous lesions. Their cytological diagnosis is difficult because of their architectural and cytological complexity, as well as the lack of experience of many cytopathologists in this field. The aim of this study was to determine the significance of Papanicolaou (Pap) smears in the diagnosis of glandular FGT lesions. Methodology: All Pap smears reported during the period of January 2012 to December 2013 were retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…Some studies also reported higher malignancy rates than expected in AGC cases. Suresh et al reported a 66.7% malignancy rate, while Selvaggi and Kirwan reported malignancy rates of 78% and 81.6%, respectively, but similar with other studies, our study showed that endometrial cancer was the most common cancer 21‐23 . The most common primary sites for metastatic tumours in AGC cases have been reported to be the colon and breast in the literature 8,12,13,20 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies also reported higher malignancy rates than expected in AGC cases. Suresh et al reported a 66.7% malignancy rate, while Selvaggi and Kirwan reported malignancy rates of 78% and 81.6%, respectively, but similar with other studies, our study showed that endometrial cancer was the most common cancer 21‐23 . The most common primary sites for metastatic tumours in AGC cases have been reported to be the colon and breast in the literature 8,12,13,20 …”
Section: Discussionsupporting
confidence: 89%
“…Although our results highly correlated with those reported in the literature, two points slightly differed. One difference was that our malignancy rate was slightly higher, although similar studies have been reported in the literature, albeit in small numbers 21‐23 . Another was that in the literature, the second most common tumour location in almost all of the studies was the cervix after the endometrium; however, the ovary was the second most common tumour site, followed by the cervix, in our study.…”
Section: Discussionsupporting
confidence: 43%
“…The malignancy rate recorded by Suresh et al. was 66.7%, 17 whereas the rates reported by Selvaggi et al. and Kirwan et al.…”
Section: Discussionmentioning
confidence: 84%
“…The incidence of AGC on cytology in our study was 1.86%, similar to the 0.08% to 2.1% incidence quoted in international literature. [ 5 6 7 8 9 10 11 ] As per Suresh et al .,[ 12 ] the rate of atypical glandular cells turning out to be malignant was 66.7%, whereas Selvaggi[ 13 ] and Kirwan et al . [ 14 ] reported malignancy rates of 78% and 81.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%